2015
DOI: 10.1039/c5cp05325k
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cations on NO2 production from the photolysis of aqueous thin water films of nitrate salts

Abstract: The photochemistry of nitrate ions in bulk aqueous solution is well known, yet recent evidence suggests that the photolysis of nitrate may be more efficient at the air-water interface. Whether and how this surface enhancement is altered by the presence of different cations is not known. In the present studies, thin aqueous films of nitrate salts with different cations were deposited on the walls of a Teflon chamber and irradiated with 311 nm light at 298 K. The films were generated by nebulizing aqueous 0.5 M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 106 publications
1
20
0
Order By: Relevance
“…The quantum yields of solid-phase nitrate photolysis are four orders of magnitude lower than those of aqueous phase one. 82 Nonetheless, emissions of gaseous NO 2 at >1 ppb min −1 83 and HONO at < 0.06 ppt min −1 84 are possible from solid-phase nitrate photolysis when thin water films or so-called surface adsorbed water (SAW) are present on the solid surface. While the exact role of SAW in nitrate photolysis remains poorly understood, the presence of SAW likely promotes the dissolution of solid nitrate to form aqueous nitrate in SAW.…”
Section: Factors Affecting Particulate Nitrate Photolysismentioning
confidence: 99%
See 2 more Smart Citations
“…The quantum yields of solid-phase nitrate photolysis are four orders of magnitude lower than those of aqueous phase one. 82 Nonetheless, emissions of gaseous NO 2 at >1 ppb min −1 83 and HONO at < 0.06 ppt min −1 84 are possible from solid-phase nitrate photolysis when thin water films or so-called surface adsorbed water (SAW) are present on the solid surface. While the exact role of SAW in nitrate photolysis remains poorly understood, the presence of SAW likely promotes the dissolution of solid nitrate to form aqueous nitrate in SAW.…”
Section: Factors Affecting Particulate Nitrate Photolysismentioning
confidence: 99%
“…83 Richards et al found that thin films (∼800 nm) of RbNO 3 and KNO 3 produce more gaseous NO 2 than those of Mg(NO 3 ) 2 and NaNO 3 , and Ca(NO 3 ) 2 . 83 Molecular dynamics simulations suggested that cations can regulate the surface propensity of nitrate anions. 66,101 For instance, the concentration of nitrate anion in the interface region of 2 M KNO 3 thin film could be ten times higher than that of 2 M NaNO 3 .…”
Section: Factors Affecting Particulate Nitrate Photolysismentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, experiments in thin water films containing nitrate, chlorine, and bromine salts have shown that the photolysis of NO 3 – occurs much faster at interfaces than in the bulk, ,, with J values ranging between 1.2 × 10 –3 and 3 × 10 –6 s –1 , depending on the features of the interface. ,,, A potential explanation for this enhancement is associated with the solvation of nitrate anion. In bulk water, nitrate is surrounded by a solvent cage that facilitates both the recombination of the NO 2 and OH radicals produced by reaction and their deactivation by collision with solvent molecules, thus decreasing the photolysis quantum yield. ,,, MD simulations have shown that when halide anions (especially bromide) are present, nitrate ions are dragged closer to the interface so that the water solvent cage surrounding them is reduced, , arguably making the escape of NO 2 to the gas phase easier. ,, Nevertheless, despite the large amount of work done on nitrate photochemistry, open issues remain that are not yet completely understood. For instance, it was recently shown that an important part of nitric acid remains undissociated at the air–water interface, , and the relevance of the corresponding photochemistry is still undetermined.…”
Section: Photochemistry Of Oh Precursorsmentioning
confidence: 99%
“…[294][295][296][297][298][299] For example, nitrate ion photolysis at interfaces is more efficient than in the bulk, and is inuenced by the presence of halide ions. [294][295][296][297][298][299] However, it should be noted that whether nitrate ions are enhanced at the interface in water is somewhat controversial, [300][301][302] and could depend on cluster size, for example.…”
mentioning
confidence: 99%